O jogo como recurso pedagógico na formação de professores de matemática - Vasconcelos, Francisco Ricardo Nogueira de (2011)
The use of mathematics games enables students to be in a proper enviroment for building and reelaborating learning, so helping out their development of cognitive structures to enable them to generelize conceptual information and turning, above all, the teacher a mediator of the process of organization and elaboration of mathematical ideas. This research has as main objective to investigate if the Mathematics Teacher Formation Course at Universidade Estadual do Ceará is preparing its undergradute students, prospective teachers, to the use of games in regular math classes. To collect data we carried out a study of the course syllabus matrix and the political pedagogical project, as well as a minicourse on how to use mathematics games to 23 students. The tools used were three questionaires, besides film footage and photographic recording. The outcomes show that the Teacher Formation Course does not prepare adequately its undergradute students, prospective mathematics teachers, on the use of games in class; the minicourse and the games used had a good level of acceptance by the participants. Final considerations highlight that the use of mathematics games can not be taken as an aim itself but as a pathway to promote significant learning.